2012
DOI: 10.1017/s0950268812000519
|View full text |Cite
|
Sign up to set email alerts
|

Bartonellainfection in urban and rural dogs from the tropics: Brazil, Colombia, Sri Lanka and Vietnam

Abstract: SUMMARYDogs can be infected by a wide range ofBartonellaspp., but limited studies have been conducted in tropical urban and rural dog populations. We aimed to determineBartonellaantibody prevalence in 455 domestic dogs from four tropical countries and detectBartonellaDNA in a subset of these dogs.Bartonellaantibodies were detected in 38 (8·3%) dogs, including 26 (10·1%) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Although cats are known to play a major role as B. henselae reservoirs in Chile [13], our results suggest that this species is also circulating in domestic dogs from the country. As observed before in Brazil [9] and Colombia [8], and described in Africa and Asia [1], rural and stray dogs, such as the dogs from Valdivia Province, are more likely to be infected or seroreactive to Bartonella spp. Bartonella vinsonii subsp.…”
Section: Epidemiology and Infection 1203supporting
confidence: 68%
“…Although cats are known to play a major role as B. henselae reservoirs in Chile [13], our results suggest that this species is also circulating in domestic dogs from the country. As observed before in Brazil [9] and Colombia [8], and described in Africa and Asia [1], rural and stray dogs, such as the dogs from Valdivia Province, are more likely to be infected or seroreactive to Bartonella spp. Bartonella vinsonii subsp.…”
Section: Epidemiology and Infection 1203supporting
confidence: 68%
“…Dogs experimentally infected with single species of Bartonella did not develop cross‐reactive antibodies against other species, but the extent to which serologic cross‐reactivity versus co‐exposure to multiple Bartonella species occurs in naturally infected dogs is unknown. Previous studies have shown poor associations between seroreactivity and bacteremia, with antibody reactivity to Bartonella species antigens detected in ≤50% of dogs and humans in which active infection with B. vinsonii subsp. berkhoffii and B. henselae can be documented .…”
Section: Discussionmentioning
confidence: 94%
“…henselae, when combined with B. quintana, accounts for over 90% of Bartonella endocarditis cases (107). Bartonella species in general have wide geographic distribution, possibly due to the geographic specificity of their respective hosts and vectors (156)(157)(158)(159)(160)(161)(162). For example, DNA of several species of Bartonella was isolated from bat flies and bats in Africa, Asia, Europe, and both North and South America (163).…”
Section: Epidemiology Of Bartonella Endocarditismentioning
confidence: 99%